Word Meaning Relations in Sindo Newspaper Editorial Text - Diah Zuikaningsih; Prihadi Prihadi; Teguh Setiawan (CV. Publikasi Indonesia, 2024)
News in the form of editorial texts or headlines in the Sindo Newspaper on semantic meaning relations. This study aims to describe the variety of word-meaning relationships in the editorial text of the April 2023 edition of the Sindo Newspaper. This study uses a descriptive qualitative method with text analysis research. The data of this study are words and phrases in sentences in the headline that show the relationship of meaning. The words and phrases in question are the words and phrases contained in the news content. The data source for this research is the headline in the April 2023 edition of the online-based Sindo Newspaper. The data collection technique in this study uses documentation and literature study techniques. Based on data analysis, various word-meaning relationships were obtained in the form of synonyms, antonyms, hyponyms, hyponyms, economies, metonyms, polysemia, collocation, and redaction.